Dramatic Universes. Towards a Rhetoric of Fictional Authentication (Castilla. Estudios de Literatura, 2012)
This paper deals with the fictional authentication systems/procedures of the dramatic mode. Stage presence constitutes the basic legitimation criterion of dramatic existence, though not all the motifs of the fable can be displayed directly on stage. Western theatrical tradition has developed authentication conventions of great economy in figures of representation such as the Prologue, the Chorus or the Narrator/epic commentator, whose statements are addressed to the spectators (or readers), as well as in statements of characters that are not addressed to other characters, such as the monologue, the aside, and the appeal to the audience.